Family Presence During Resuscitation (FPDR) terhadap Kepuasan Keluarga - Hamdani Hamdani; Nani Nurhaeni; Dessie Wanda (Journal of Telenursing (JOTING), 2023)
This study aims to provide an overview of the effect of Family Presence During Resuscitation (FPDR) on family satisfaction. The research method is a systematic review using the PICO format, and data extraction is carried out by critically assessing articles using JBI critical appraisal tools. The results showed that FPDR influenced family satisfaction. The level of satisfaction of families who implemented FPDR was higher than families who were not present during cardiopulmonary resuscitation. In conclusion, FPDR can increase family satisfaction with health services. Families want to be offered the option of getting FPDR, but the application of FPDR still needs to be improved because they have to consider the readiness of FPDR services. Keywords: Family Presence During Cardio Pulmonary Resuscitation, Satisfaction, Experience, Perception, Cardio Pulmonary Resuscitation, CPR